Analisis Kebijakan Pemerintah terhadap Pemenuhan Hak atas Pendidikan di Tengah Prioritas Anggaran Program Makan Bergizi Gratis - Amrizal, Amrizal; Asiah, Asiah; Sopian, Sopian (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2026)
This study analyzes government policy regarding the allocation of education budgets for the Free Nutritious Meal (MBG) Program and its implications for fulfilling the right to education in Indonesia. The MBG program is a cross-sectoral policy aimed at improving students’ health and learning readiness, but its inclusion in the education budget raises questions about the prioritization of public funds in line with constitutional mandates. This research uses a normative legal method with statutory and conceptual approaches, analyzing regulations, doctrines, and academic literature related to the right to education, public policy, and education budgeting. The findings indicate that the MBG program positively supports the learning process; however, education budget management must remain focused on the core needs of the national education system, including improving teacher quality, facilities, and learning outcomes. Therefore, integrating human development programs through MBG should be implemented proportionally to remain consistent with constitutional mandates and ensure the fulfillment of the right to education for all citizens.